Improving Listening Skills Through English Song at Seven Grade MTs Babusalam Besilam Academic Year 2022/2023 - Ade Syafirna; Edi Suprayetno; Jonris Tampubolon (English Lecturers and Teachers Association (ELTA), 2023)
This journal's purpose is to learn how music can be used to develop listening skills. One of the four foundational English language skills is listening. It appears that speaking, reading, and writing are among the other skills. These fundamental abilities are broken down into productive skills like speaking and writing and receptive skills like listening and reading. Songs and music are essential components of development and education. The use of music in the classroom has various benefits. The use of songs in the teaching of foreign languages has both supporters and opponents. The use of songs in the educational process, particularly during listening lessons, helps students develop their listening skills as one of their valuable techniques to deal with listening skill issues English songs are engaging, so they can encourage participation from the students and help them perform better on listening tasks. However, using songs to aid in listening has drawbacks. For example, popular music isn't always accurate, and inadequate sound systems in classrooms can interfere with listening to music. Keywords: Listening Skill, English Song, English Students